O desafio de avaliar políticas públicas: conhecer, julgar, "publicizar" e aprimorar - Branco, Noemi Nascimento (2005)
This presente research investigate if the head teachers election process have been mading with the participation of the school segments – parents, students, teachers and employees in day-today decisions of the education action, in objective of democracy of the management. This discussion is important for us in the sense that, how the head teachers election has been happen, since 1995 in the Ceará State, and the sametime, if it is possible to see how the school central actors had worked on the participation question. In the methodology we made bibliographyc and local research and in that time, we applied questionnaire and we made interview with teachers, students, employees, parents and members of the management nucleus of two state public schools: São Paulo school and São Caetano school: the results shows that, although they accept and they think that the election process of head teachers is positive, theirs participation in the schools direction is not full yet, because they don’t know how the education process happens; or because they don’t have interest on the school direction, because they don’t feel like participating in the education process; or because they are not envolved. The results make us to re-direction the participation practice, in the sence of make real the collective make in the school activities, that impose beliefs and values changes, understanding the participation in a view of consolidation and realization of the democratic management, that goes over of the head teachers choise by direct elections.